Development of Electrospun Quaternized Poly(vinyl alcohol)/Poly(acrylamide-co-diallyldimethylammonium chloride) Anion Exchange Membranes for Alkaline Fuel Cells - Asep Muhamad Samsudin; Viktor Hacker (Nanomaterials, 2025)
Anion exchange membrane fuel cells (AEMFCs) have garnered significant attention for their potential to advance fuel cell technology. In this study, we developed and characterized anion exchange membranes (AEMs) composed of quaternized poly(vinyl alcohol) (QPVA) electrospun nanofiber mats with poly(acrylamide-co-diallyldimethylammonium chloride) (PAADDA) as a matrix filler for interfiber voids. The objective was to investigate the effect of varying PAADDA concentrations as a matrix filler for interfiber voids on the structural, mechanical, and electrochemical properties of QPVA-based electrospun AEMs. Membranes with various concentrations of PAADDA were fabricated and extensively characterized using FTIR, SEM, tensile strength, water uptake, swelling degree, ion exchange capacity (IEC), and hydroxide ion conductivity (σ). FTIR confirmed the successful incorporation of PAADDA into the membrane structure, while SEM images showed that PAADDA effectively filled the voids between the QPVA fibers, resulting in denser membranes. The results indicated that the eQPAD5.0 membrane, with the highest PAADDA content, exhibited the best overall performance. The incorporation of PAADDA into QPVA-based electrospun AEMs significantly enhanced their mechanical strength, achieving a tensile strength of 23.9 MPa, an IEC of 1.25 mmol g−1, and hydroxide conductivity of 19.49 mS cm−1 at 30 °C and 29.29 mS cm−1 at 80 °C, making them promising candidates for fuel cell applications.